Breast cancer morbidity and mortality in rural Ethiopia: data from 788 verbal autopsies - Wondimu Ayele; Amand Führer; Gabriele Anna Braun; Franziska Formazin; Andreas Wienke; Lesley Taylor; Susanne Unverzagt; Adamu Addissie; Eva J. Kantelhardt (BMC, 2022)
Abstract Introduction In Ethiopia, breast cancer is the leading cause of cancer among women. Little is known about the duration of disease and symptoms of patients who died from breast cancer in rural Ethiopia. The objective of this study was to assess breast cancer mortality with a particular focus on the self-reported duration of illness including suffering of symptoms, and need for medical care. Methods The cause of death was determined among randomly selected Ethiopian women residing in western Ethiopia. A modified standard verbal autopsy (VA) questionnaire was completed by women whose sisters had died. The questionnaires were reviewed by two independent local physicians to assign a cause of death. We analyzed pattern of cause of deaths, duration of suffering, symptoms, and treatment received. Result In our study, the age at death was very similar to other population-based data from Ethiopia. We found 32% of 788 deaths were caused by communicable diseases, 12.1% by neoplasms, and 9.4% by pregnancy/maternal mortality. Breast cancer was the second leading neoplasm, responsible for 21 (2.7%) of all deaths (95% CI 1.5-3.7%), and was among the top five causes of non-communicable deaths. The median age of breast cancer death was 37 years, younger than for other causes of death. The median duration of illness with breast cancer was around 1 year. This was substantially more compared to the duration of infectious diseases, but less than the duration of reproductive neoplasms, diabetes, and epilepsy. Discussion/conclusion Breast cancer deaths are common causes of death in women of rural Ethiopia. When assessing the total duration of illness according to specific causes of death, breast and other cancers accounted for a large share of the burden. This has practical implications and highlights the need for palliative care for cancer patients. Substantial efforts are necessary to improve early detection and treatment for breast cancer to reduce premature death in women.